Narrativas autobiográficas de Teresa de Ávila: veredas e desafios para o processo de espiritualização na contemporaneidade - Lima, Daniel Mattos de Araújo (2013)
This thesis deals with the autobiographical narratives of Teresa of Avila and their meeting and mismatch places with the emerging sense of spirituality of the subjects in the present. The narrative of Teresa of Avila, a 16th century Catholic saint, reveals important meanings to think about the current process of spiritualization in the field of human formation by the development of the integral human being as a paradigm. The understanding of this narrative, which bills itself as a complex whole in which they are inserted fundamental symbolic elements for recognition of spiritualizing processes of the Hispanic, occurred from the threefold mimesis model of Paul Ricoeur (1994) and demanded also a deep hermeneutic work, as Thompson (1995). The general objective of this study was to understand the autobiographical narratives of the saint in three of her main books – Book of Life (1562), Interior Castle or Addresses (1577) and Foundations (1582) – in order to get clues and possibilities to broaden the understanding about human formation in contemporary times, focusing on the process of spiritualization. The 16th century, in this sense, revealed the new qualities of experience of itself in a more dynamic and open world if compared to the medieval past. Thus, the Carmelite autobiographical production involved a complex plot that included the relationship with the confessors, with the Inquisition, with families, institutions and spiritual people of the time. Carmelita's desire of founding new monasteries was something remarkable, revealing the gradual appropriation of the uniqueness of her spiritual path and the dichotomy between action and prayer overcoming. Her narrative and life trajectory showed the body, prayer and works as constituents categories. These categories analysis developments resulted in a reflection on the possibilities contained in the spiritualizing processes in contemporary times, bringing up a kind of sensitivity of creative production of himself through the narrative that was named autopoietic sensitivity. An analysis of the beliefs subjectivation processes today revealed important composition of religious identities possibilities inserted into a dynamic historical processuality that admits more tenuous ties with the institution. The body, the prayer and the works are inserted into the ordinary people daily dynamics who seek the challenge of giving coherence to their spiritual biographic trajectories amid a current context of experiences fragmentation.